Transformation for sustainable business and management practices : exploring the spectrum of industry 5.0 - Saini, Aarti; Garg, Vikas (Emerald publishing Limited, 2023)
Since the introduction of Industry 5.0, there has been a greater emphasis on the human-centric view in human-machine collaboration. As society has benefitted from technological advancements in all aspects of industrial sectors, there has been a rethinking of the role human beings should play in future evolutions.